2010
DOI: 10.1007/s12206-010-0214-x
|View full text |Cite
|
Sign up to set email alerts
|

Cooling performance of R510A in domestic water purifiers

Abstract: Cooling performance of R510A is examined both numerically and experimentally in an effort to replace HFC134a in the refrigeration system of domestic water purifiers. Although the use of HFC134a is currently dominant, it is being phased out in Europe and most developed countries due to its high potential contribution to global warming. To solve this problem, cycle simulation and experimental measurements are conducted with a new refrigerant mixture of 88%RE170/12%R600a using actual domestic water purifiers. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Park et al [14] numerically and experimentally examined the cooling performance of R510A as a replacement for R134a in the refrigeration system of domestic water purifiers. Test results showed that, due to the small internal volume of the domestic water purifier's refrigeration system, the system performance with R510A is greatly influenced by the amount of charge.…”
Section: Introduction / Uvodmentioning
confidence: 99%
“…Park et al [14] numerically and experimentally examined the cooling performance of R510A as a replacement for R134a in the refrigeration system of domestic water purifiers. Test results showed that, due to the small internal volume of the domestic water purifier's refrigeration system, the system performance with R510A is greatly influenced by the amount of charge.…”
Section: Introduction / Uvodmentioning
confidence: 99%
“…Results of tests found that energy usage and compressor discharge temperature of R510A are 22.3 percent and 3.70 degrees Celsius lower than those of HFC134a with 50% of the refrigerant charge, respectively. HFC134a is a tremendous long substitute for R510A, which necessitates slight alteration to the refrigeration system of household water purifiers compared to HFC134a [16].…”
Section: Introductionmentioning
confidence: 99%